The Evidence of the Ugaritic Tablet СТА 19 (KTU 1.19): A Reconsideration of the Kinnereth Hypothesis - Dressler, H. H. P.
read III 41 yqbr nn.bṯugt bknh (not bmdgt bknrt), 'he buried him with the howling of his lament'.